Clinical results of two different three-dimensional titanium plates in the treatment of condylar neck and base fractures: A retrospective study. Issue 8 (August 2020) - Burkhard, John Patrik Matthias; Koba, Sabine; Schlittler, Fabian; Iizuka, Tateyuki; Schaller, Benoît
Abstract: Purpose: The aim of this study was to examine two different types of three-dimensional plate for their suitability for the treatment of condylar neck and base fractures, and to evaluate the most frequent complications, while considering three different surgical approaches. Materials and methods: This retrospective study was conducted in patients who received two different types of three-dimensional plate for the treatment of condylar neck and base fractures, using three different surgical approaches, from January 2016 to December 2018. Medical records were obtained during an average follow-up period of 9 months after the traumatic event, with data collected on factors affecting success and failure of miniplates, clinical outcome parameters, and complications. Results: A total of 43 fractures (38 patients) were examined. No differences were found between the two plate designs (mean = 0.093, SD = 0.294, p = 0.562). All fractures achieved complete bone healing, but in four cases, a revision operation had to be performed. No significant complications were found regardless of the surgical approaches chosen. There was no correlation between plate system (mean = 0.419, SD = 0.492, p = 0.497) or surgical access (mean = 0.163, SD = 0.432, p = 0.247) and the occurrence of facial nerve palsy found. Due to the extraoral approach used, permanent facial nerve palsy was reported in one case. With the intraoral approach, one case of transient facial paresis was observed. No facial palsy was observed in patients treated via a preauricular approach. Conclusion: Deltoid and trapezoid plates seem to perform equally in the treatment of condylar neck and base fractures.